A Case of Primary Amyloidosis Involving Liver, Stomach, Intestines, and Heart without Evident Kidney Involvement - L. S. Kholopov; N. B. Gubegrits; O. A. Dyadyk; Yu. E. Chirkov; Yu. V. Tsohoyeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
Aim. Systemic amyloidosis caused by the synthesis and deposition of immunoglobulin light chains (AL amyloidosis) is a relatively rare disease that involves heart, kidneys, peripheral nervous system, gastrointestinal tract, and has a large number of various clinical manifestations. We present a clinical case of systemic AL amyloidosis with a predominant involvement of liver, stomach, intestines, and heart in a Caucasian female.Key points. A Caucasian woman presented to clinic with severe general weakness, abdominal pain, diarrhea, sudden weight loss, and palpitation. Initial examination revealed a duodenal bulb ulcer complicated by bleeding and polyps in the retrobulbar part of duodenum. Decreased hemoglobin levels, elevated levels of alkaline phosphatase, gamma-glutamyltransferase, and N-terminal prohormone of brain natriuretic peptide, signs of heart failure with preserved ejection fraction, and hepatomegaly became the basis for a clinical suspicion of AL amyloidosis and puncture liver biopsy. Histochemical and immunohistochemical studies of liver, stomach, and duodenum biopsy specimens confirmed AL amyloidosis. Timely diagnosis made it possible to conduct a specific therapy with melphalan plus dexamethasone, get a satisfactory response and improve the patient’s condition.Conclusion. A thorough examination of patients along with a pathomorphological and immunohistochemical study of the biopsy specimens is the basis for confirming the diagnosis of AL amyloidosis, selecting the proper therapy, improving the condition of patients and their survival.